Investigation on musculoskeletal discomfort and ergonomics risk factors among production team members at an automotive component assembly plant - Fazilah, Abdul Aziz; Z., Ghazalli; N. M. Zuki, N. M.; Amri, Isfar (Institute of Physics Publishing, 2017)
Musculoskeletal discomfort (MSD) is a very common condition in the automotive industry. MSD affects the worker’s health, well-being and decreases productivity. The main objective of this study is to identify the prevalence of MSD and ergonomics risk factors among production team members at a selected automotive component manufacturer in Malaysia. MSD data were collected by conducting structured interviews based on the Cornell Musculoskeletal Disorder Questionnaire (CMDQ). The production team members who achieved a total discomfort score for all body regions of more than 100 were selected for job task assessment. The physical exposure risk factors of work related musculoskeletal disorders (WMSD) were evaluated by using Quick Exposure Check (QEC) techniques. The results of the study identified severe MSD associated with production assembly team members. It is expected that the prevalence of MSD for these production assembly team members concerned lower back (75.4%), upper back (63.2%), right shoulder (61.4%), and right wrist (60%). The QEC analysis discovered that about 70% of job tasks had very high risks for neck posture and 60% had high risks for the back (in moving condition) and shoulder/arm postures. 80% of respondents produced a high score for exposure risk to vibration. As a conclusion, the main implication of the current study is that special attention should be paid to the physical and psychosocial aspects in production team members with musculoskeletal discomfort to improve their safety, health, and well being, maintain work ability and productivity.